Differential Responses of Thalamic Reticular Neurons to Nociception in Freely Behaving Mice - Huh, Yeowool; Cho, Jeiwon (Frontiers in Behavioral Neuroscience, 2016)
Pain serves an important protective role. However, it can also have debilitating adverse effects if dysfunctional, such as in pathological pain conditions. As part of the thalamocortical circuit, the thalamic reticular nucleus (TRN) has been implicated to have important roles in controlling nociceptive signal transmission. However studies on how TRN neurons, especially how TRN neuronal subtypes categorized by temporal bursting firing patterns—typical bursting, atypical bursting, and non-bursting TRN neurons—contribute to nociceptive signal modulation is not known. To reveal the relationship between TRN neuronal subtypes and modulation of nociception, we simultaneously recorded behavioral responses and TRN neuronal activity to formalin induced nociception in freely moving mice. We found that typical bursting TRN neurons had the most robust response to nociception; changes in tonic firing rate of typical TRN neurons exactly matched changes in behavioral nociceptive responses, and burst firing rate of these neurons increased significantly when behavioral nociceptive responses were reduced. This implies that typical TRN neurons could critically modulate ascending nociceptive signals. The role of other TRN neuronal subtypes was less clear; atypical bursting TRN neurons decreased tonic firing rate after the second peak of behavioral nociception and the firing rate of non-bursting TRN neurons mostly remained at baseline level. Overall, our results suggest that different TRN neuronal subtypes contribute differentially to processing formalin induced sustained nociception in freely moving mice.